Pernikahan Dini Menghambat Pertumbuhan Pada Anak Usia 2 Tahun - Hasniati, Hasniati; Syahriani, Syahriani; Nurbaya, Siti; Fitriani, Fitriani; Asnuddin, Asnuddin (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Early marriage, which is marrying children who are still under 20 years old, shows the immaturity of parents' thinking. This situation triggers a parental problem-solving response based on immature thinking. Growth is an increase in the size and number of cells, as well as intercellular tissue, which means an increase in physical structure so that weight (kg) length (cm) and head circumference (cm) can be measured. This study aims to find out